Análise estabiliométrica de atletas de futsal ouvintes e surdos - Emiliavaca, Alex Luís (2020)
Body control is essential for maintaining the balance of the human being when standing still, preparing to move, moving or preparing to stop moving. The objective of the study was to analyze the stabiliometric measures of congenital or hearing impaired futsal athletes and amateur hearing athletes. The initial hypothesis of Deaf people with different parameters than listeners was partially confirmed. The stabiliometric parameters were evaluated using the baropodometry platform. The study is quantitative in nature, descriptive-analytical, observational, case-control. The research subjects were male athletes aged 18 to 40 years. One group was formed by non-hearing athletes who have congenital disabilities or who are hearing impaired participating in the 2019 Gaúcha Futsal League for the Deaf in 2019. The second group was formed by hearing futsal athletes participating in the Municipal Futsal Championship of Sertão/RS 2019 The sample size was calculated for independent samples. The sample was defined with 122 subjects, of which 62 were deaf and 60 listened. The data were analyzed for normality using the Komogorov-Smirnof test and the homoscedasticity of the groups' variance was analyzed using the Levene test. The quantitative data were analyzed using statistical techniques described and inferential of the univariate and bivariate type, Anova Test. The H0 hypothesis was refuted if the significance value was p ≤ 0.5. The body mass index showed no statistically significant difference between the groups (p = 0.904). The results showed higher and statistically significant values for the maximum pressure for the left foot of the group of non-listening athletes (p = 0.001). Deaf people have fluctuations in terms of the body pressure center: distance from the center of the body pressure, the center of gravity of the body, the average speed, the center of gravity of the left and right feet. Deaf athletes, when they present a greater displacement of the body pressure center, present greater differences in the balance parameters.